CHALLENGES OF GAME-BASED LEARNING STRATEGIES IN TEACHING MATHEMATICS IN PRIMARY SCHOOLS IN NKANU WEST LOCAL GOVERNMENT AREA OF ENUGU STATE - Oluwatayo, Jennifer C.; Anyikwa, Ngozi E.; Obidike, Ngozi. D. (Journal of Early Childhood and Primary Education, 2020)
The study was designed to determine the challenges of game-based learning strategy in teaching mathematic in primary schools in Nkanu West Local Government Area of Enugu State. Three research questions guided the study. Descriptive survey research design was adopted. The population of the study comprised of 665 primary school teachers in 54 public primary schools in Nkanu West Local Government Area of Enugu State.  A sample of 200 primary school teachers was used for the study using simple random sampling technique. The researchers developed an instrument titled â€œChallenges of Game-Based Learning Strategy in Teaching Mathematics in Primary School (CG-BLSTMPS)â€ Questionnaire. The instrument was validated by three experts. Cronbach Alpha was used to measure the internal consistency and co-efficient of 0.92, 0.77 and 0.79 were obtained with an overall co-efficient of 0.83. Data collected were analyzed using weighted mean to answer the research questions and standard deviation to determine the homogeneity or otherwise of the respondents' views. Findings of study revealed that teachers do not use the available games such as circle race game, binary tic tac game geo-board game among others to teach mathematics in primary schools. Findings of the study also revealed that teachers are faced with challenges of using game-base to teach mathematics which includes; lack of teacherâ€™s knowledge or proficiencies on the use of game, inadequate time for instruction of using game and large class size among others. The study also disclosed that adequate spaces for game should be provided to enable teachers use game in teaching mathematics and gaming materials such as software, hardware, slide, and boards among others should be made available for teachers to use in teaching mathematics among others. Based on the findings, it was recommended among others that Enugu State Government in conjunction with Parent Teachers Association (PTA) should provide adequate and functional game materials and infrastructural facilities in primary schools in order to enable teachers use diversify strategy to teach mathematics to pupils for better understanding which will stimulate effective teaching and learning process.
Keywords: Primary Education; Mathematics; Teaching Strategy; Game-Based